Building Last Mile Livestock Extension Services for Rural Communities in Jharkhand, India - Leitch, Helen (World Bank, Washington, DC, 2020)
Jharkhand's livestock production is in the hands of marginal and landless farmers with women accounting for over 70 percent of the production. The JOHAR project aims to enhance and diversify household income through the livestock component to target nearly 57,000 beneficiaries for enhancing productivity and accessing markets in selected value chains (broilers, layers, pigs, goats and dual purpose backyard poultry). Given the major role of women, especially from marginal and landless households, JOHAR livestock activities target over 90 percent female beneficiaries. While local service providers are an important feature in all livestock related investments the Bank finances, the JOHAR model is believed to be the most comprehensive and successful of all. This note highlights JOHAR's livestock activities, the JOHAR Pashu sakhi model, lessons learned and what makes the JOHAR model different.